Brazilian Nursing Process Research Network contributions for assistance in the COVID-19 pandemic - Barros, Alba Lúcia Bottura Leite de; Silva, Viviane Martins da; Santana, Rosimere Ferreira; Cavalcante, Agueda Maria Ruiz Zimmer; Vitor, Allyne Fortes; Lucena, Amália de Fatima; Napoleão, Anamaria Alves; Lopes, Camila Takao; Primo, Cândida Caniçali; Carmona, Elenice Valentim; Duran, Erika Christiane Marocco; Butcher, Howard Karl; et al. (FapUNIFESP (SciELO), 2020)
OBJECTIVE: to describe the theoretical construction process of nursing process support documents in COVID-19 care scenarios. METHODS: an experience report of the joint activity of the Brazilian Nursing Process Research Network (Rede de Pesquisa em Processo de Enfermagem) composed of Higher Education and Health Institution researchers in Brazil. RESULTS: five instruments were organized collectively, involving the elements of nursing practice (nursing diagnoses, outcomes and interventions) in assistance for community; for patients (with suspected or mild, moderate, and critical COVID-19 and residents in Nursing Homes); for nursing workers' health support, also subsidizing registration and documentation during the COVID-19 pandemic. FINAL CONSIDERATIONS: valuing the phenomena manifested by families/communities, patients and health professionals is essential for early detection, intervention, and prevention of diseases.